AN EXAMINATION OF THE CHILDREN WITH DEVELOPMENTAL COORDINATION PROBLEM AND PHYSIOTHERAPY - Kaur, Inderpreet; Singh, Sikander (International Journal of Psychosocial Rehabilitation, 2021)
It is the goal of this systematic literature review and meta-analysis to identify the kinds of physical therapy therapies that have been studied in children with developmental coordination deficits, the most prevalent factors being addressed, and if these interventions are beneficial. It was found that the PEDro and NIH quality evaluation measures were used to assess the quality of the studies that were screened using the MEDLINE, PEDro, CINAHL, SPORTDiscus, PsycINFO, or Cochrane Library databases. In order to assess systematic reviews, researchers employed AMSTAR and then performed a meta-analysis. From the articles that were analyzed, 29 articles of moderate to high quality made it into the qualitative analysis. Children with DCD benefit from both task-oriented and motor skill training-based therapies when it comes to enhancing their motor function. The meta-analysis included data from 14 studies, all of which supported the efficacy of physical therapy treatments in the fight against inactivity. Physical treatment for children with DCD should include both task-oriented and conventional approaches, according to the findings. Individual children’s needs must be well defined in interventions in physical therapy settings.